Efectos de la nutrición mineral sobre la eficiencia en el uso del agua de verdeos de invierno (Semiárida, 2020)
Mineral nutrition has a positive influence on the water use efficiency of winter greens, in relation to dry matter production and its quality. The displacement of livestock farming by agriculture towards soils with lower potential would be leading to lower efficiency in the use of water for the production of forage and meat in mixed systems. The work objective was to evaluate the effect of mineral nutrition (N,P) on forage production and efficiency in water use in rye established in a Haplustol Entic with medium to low contents of OM and available P. To carry out the experience, a design of three blocks was made, each one had nine fertilization treatments (N-P), using plots of 150 m^ (10 X 15m). Three nitrogen fertilization treatments were established (N0= Okg/ha; N40= 40kg/ha and N80= 80l